Service oriented architecture components and modeling can make the difference. - Arsanjani, Ali
In many respects, SOA is an evolution of the fundamental tenets governing component-based development (CBD). It also represents a quantum leap in bringing business and information technology into closer alignment through a set of SOA services grounded in business goals in support of business processes. While SOA services are visible to the service consumer, their underlying components are transparent. For the service provider, the design of components, their service exposure and management reflect key architecture and design decisions that enable services in SOA. Making these decisions requires an understanding of an SOA's components and SOA modeling to identify, classify, specify and structure service enabled components. In this article we briefly discuss the relationship between CBD and SOA, followed by a discussion of SOA architecture and design decisions. We describe the basic SOA components and building blocks and a prescriptive technique for performing SOA modeling, analysis and design for services where services are realized using components.